SISTEM PENGENDALIAN INTERN PEMERINTAH ATAS AKUNTABILITAS PENGELOLAAN KEUANGAN DANA DESA DI KECAMATAN SEMBAWA - Rita Martini; Naufal Lianto; Sukmini Hartati; Zulkifli Zulkifli; Endah Widyastuti (Universitas Muhammadiyah Malang, 2019)
The purpose of this research was to analysis the influence of government internal control system (GICS), consists of the control environment, risk assessment, control activities, information and communication, and monitoring control to accountability of village fund finance management. Sample was determined by using purposive sampling that were village government who holds a position in finance village fund in Sembawa District Banyuasin Regency, South Sumatra Province. The data were collected through questionnaires. The respondents are the head of the village, the secretary of the village, the treasurer of the village, section head, and village consultative agency. The data were analyzed by multiple linear regressions. The results showed that partially and simultaneously GICS components have significant effect on the accountability of village fund finance management.